Dendritic cell inhibition correlates with survival of colorectal cancer patients on bevacizumab treatment. - O'SULLIVAN, JACINTHA (My University, 2012)
we demonstrated that dendritic cell (DC) inhibition by tumor-conditioned media in the presence or absence of bevacizumab correlates with colorectal cancer patient survival. Monitoring the influence of the tumor microenvironment on infiltrating immune cells may offer an avenue for the discovery of biomarkers to guide the use of bevacizumab
PUBLISHED
Keywords: tumor microenvironment; dendritic cells; colorectal cancer; bevacizumab